2016
DOI: 10.1111/opo.12297
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration beyond the primary visual pathways in a population with a high incidence of normal‐pressure glaucoma

Abstract: Citation information: Boucard CC, Hanekamp S, C ´ urč ic´-ic´ic´-Blake B, Ida M, Yoshida M & Cornelissen FW. Neurodegeneration beyond the primary visual pathways in a population with a high incidence of normal-pressure glaucoma. Abstract Purpose: Glaucoma is the most common age-related neurodegenerative eye disease in western society. It is an insidious disease that, when untreated or detected too late, leads inevitably to blindness. An outstanding issue is whether glaucoma should be considered exclusively an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 56 publications
8
56
0
8
Order By: Relevance
“…The smaller FA value contralateral to the enucleated eye may be explained by the relatively smaller LGN and optic tract volumes previously demonstrated contralateral to the enucleated eye in this specific ME sample [Kelly et al, ]. Previous studies of long‐term visual deprivation have commonly interpreted a reduction in FA as the consequence of transneuronal degeneration or axonal immaturity [Boucard et al, ; Shu et al, ]. Transneuronal degeneration could certainly account for the observed change in FA if, for example, the smaller LGN contralateral to the enucleated eye supports fewer efferent fibers extending to V1, or if the reduction in visual input results in disuse atrophy.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The smaller FA value contralateral to the enucleated eye may be explained by the relatively smaller LGN and optic tract volumes previously demonstrated contralateral to the enucleated eye in this specific ME sample [Kelly et al, ]. Previous studies of long‐term visual deprivation have commonly interpreted a reduction in FA as the consequence of transneuronal degeneration or axonal immaturity [Boucard et al, ; Shu et al, ]. Transneuronal degeneration could certainly account for the observed change in FA if, for example, the smaller LGN contralateral to the enucleated eye supports fewer efferent fibers extending to V1, or if the reduction in visual input results in disuse atrophy.…”
Section: Discussionmentioning
confidence: 76%
“…The relatively weaker physiological input to the hemisphere contralateral to the nondominant eye [Toosy et al, ], or in this case, the enucleated eye, is likely compounded by changes to the visual pathway structures (e.g., optic tract and LGN) [Kelly et al, ] in the same hemisphere resulting in further reduced V1 activity [Barb et al, ]. Reduced functional activity can disrupt normal corticothalamic feedback [Cudeiro and Sillito, ], causing axonal degeneration or immaturity [Boucard et al, ; Shu et al, ], and likely results in the disorganization of the V1‐LGN tracts. Similarly, the structural changes in V1 of these ME participants may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent DTI study on NTG patients from Japan, where the disease has a high prevalence, using a similar analysis (TBSS) but a different statistical approach, decreased FA was found compared to NC in the occipital WM comprising OR and F maj but also in nonvisual areas such as CC and parietal lobe [Boucard et al, ]. Because our study on a relatively small population has an exploratory nature, we used a less conservative threshold compared with the above study.…”
Section: Discussionmentioning
confidence: 99%
“…An MRI study on the anterior visual pathway of NTG showed reduced volumetry and altered DTI measures, which correlated with RNFL thickness and VF measures [Zhang et al, ]. A more recent DTI study in NTG patients from Japan, where the disease has a high prevalence, found decreased fractional anisotropy (FA) compared with normal controls (NC) in the occipital WM comprising optic radiations (OR) and forceps major ( F maj ) but also in nonvisual areas such as corpus callosum (CC) and parietal lobe [Boucard et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The special issue also emphasised fundamental research questions that can be addressed with imaging. These included diurnal changes in ocular tissues, the use of imaging to understand and diagnose retinal disease and the extent to which the brain changes its structure and function in individuals with macular degeneration or glaucoma . In addition, contemporary themes in vision science imaging research were identified by two invited review papers featured within the special issue.…”
mentioning
confidence: 99%